Test for Gini indices against an umbrella ordered alternative. Issue 6 (2nd November 2017) - Bansal, P.; Arora, Sangeeta; Mahajan, K.
Abstract: Gini Index is a powerful tool for analysing income or wealth distribution within a country or aregion. In the present article, a test for Gini indices against an umbrella ordered alternative has been proposed. The critical points for the proposed test are computed for two parameter exponential distribution using simulation study. The size of the test is also derived through simulation. Using some transformation tecniques the proposed test can be used for som other distributionsas well. Simultaneous one-sided confidence intervals have also been constructed for the proposed test . Power of the test is also computed along with some power comparisons